UNIT 9.23 Management of Incidental Findings in Clinical Genomic Sequencing. (6th October 2015) - Krier, Joel B.; Green, Robert C.
Abstract : Genomic sequencing is becoming accurate, fast, and increasingly inexpensive, and is rapidly being incorporated into clinical practice. Incidental or secondary findings, which can occur in large numbers from genomic sequencing, are a potential barrier to the utility of this new technology due to their relatively high prevalence and the lack of evidence or guidelines available to guide their clinical interpretation. This unit reviews the definition, classification, and management of incidental findings from genomic sequencing. The unit focuses on the clinical aspects of handling incidental findings, with an emphasis on the key role of clinical context in defining incidental findings and determining their clinical relevance and utility. © 2015 by John Wiley & Sons, Inc.